Malformasi Genital Perempuan: Kasus di RSUP Dr. Sardjito Yogyakarta Tahun 2019 - Anis Widyasari; Muhammad Nurhadi Rahman; Akbar Novan Dwi Saputra; Nuring Pangastuti (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2022)
BackgroundReproductive tract malformations are rare in general population but are commonly encountered in women with infertility and recurrent pregnancy loss. Their true prevalence in the general population is not absolutely known mainly owing to methodological bias. Common uterine anomalies are important owing to their impact on fertility, and certain Mullerian malformations are particularly important because they cause serious clinical symptoms and affect woman’s quality of life. Identification of symptoms and timely diagnosis are an important key to the management of these defects. Although MRI being gold standard in delineating uterine anatomy, recent advances in imaging technology, specifically 3-dimensional ultrasound, achieve accurate diagnosis. Surgical management depend on the type of anomaly and its complexity and also involves multiple specialties; thus, patients should be referred to centres with experience in the treatment of complex genital malformationsObjectiveDetermined the description of cases of female genital malformation at Dr. Sardjito Hospital in 2019.MethodThis is descriptive study. The subject in this study were all new patient with female genital malformation at Obgyn Polyclinic Dr. Sardjito Hospital January-December 2019. Obtained 30 cases of female genital malformation.ResultThere is 30 cases of genital malformation in 2019. They were 4-44 years with mode at group 16-20 years. They consist of vaginal and cervicovaginal agenesis 14 cases, Mayer-Rokitansky-Küster-Hauser (MRKH) Syndrom 6 cases, hematometra of hemiuterine 4 cases, Herlyn-Werner-Wunderlich (HWW) syndrome 3 cases, imperforate hymen, didelphys uterus and genital ambiguous each 1 case. Five cases of cervicovaginal agenesis have been done sigmoid vaginoplasty, all of them have good sexual function after procedure. One case MRKH syndrome has been done sigmoid vaginoplasty with good sexual function after that. Two cases HWW syndrome have been surgical treatment that are vaginal septectomy and vaginal septectomy with laparascopic cystectomy.ConclusionThe correct knowledge of embryology of the genitourinary is essential for the understanding, study, diagnosis and management of genital malformations, especially complex ones and those that lead to reproductive problems. Surgical techniques for correcting genital malformations depend on the type of anomaly and complexity.